The Impact of Lifestyle, Financial Literacy, and Ease of Use of E-Payment on E-Wallet Users' Consumptive Behavior in the Millennial Generation - Ulum, Ima Fidatul; Solekah, Nihayatu Aslamatis (MEC-J (Management and Economics Journal), 2024)
This research aims to determine the influence of ease of use of e-payment, lifestyle and financial literacy on consumer behaviour. This research uses a quantitative approach with a survey method. The population in this study is the millennial generation who live in Malang Raya. The number of samples taken was 275 respondents. The data analysis technique uses the SEM-PLS analysis technique. This research shows that ease of use of e-payment has a positive and significant effect on consumer behaviour. Lifestyle has a positive and significant impact on consumer behaviour. Financial literacy has a positive and significant effect on consumer behaviour. The findings in this research imply that e-wallet provider companies hope to continuously improve and maintain service quality and literacy related to e-wallet operations, especially for the millennial generation, who can efficiently operate e-wallets to support their consumptive lifestyle behaviour